Development of Entrepreneurship Education Teaching Material Based on the National Resilience and Amare Culture - Yosua Damas Sadewo; Pebria Dheni Purnasari; Bella Ghia Dimmera (JETL (Journal of Education, Teaching and Learning), 2020)
The development of teaching materials is important to create a learning process that suits the needs of STIM Shanti Bhuana. The Entrepreneurship Study Program of STIM Shanti Bhuana has not yet possessed teaching materials that represent the characteristics of the institution, i.e. national resilience and Amare culture. Therefore, needed the development of a valid teaching material that can improve students' learning outcomes, and has characteristics that can be used. Borg and Gall’s model of development is employed in this study which is summarized into three major steps to ease the study. The steps include the study of introduction, product development, and product validation. This study shows that this developed teaching material is valid. The result is obtained through the analysis upon the validation forms. From 9 validations, the score of 4.49 is obtained. The value means that the teaching material is appropriate and can be used. The analysis result on the learning mastery, after the students attend the classes integrating the teaching material, is 75%. Through the N-gain exam, it is known that there is an improvement between the pre-test and post-test with a value of 0.40. The percentage value of the improvement is 33.33%. The characteristics of the development of the National Resilience and Amare Culture-Based Entrepreneurship Education, based on the questionnaire, shows that the developed teaching material provides a good effect on the students. Through the measurement on the score from the questionnaire, it is gained the value of 83.8. Therefore, it can be concluded that the developed teaching materials are valid, can improve students' learning outcomes, and are easily used by the students.